Clima familiar y relaciones interpersonales de estudiantes del VI ciclo de la Escuela Profesional de Trabajo Social. Universidad Nacional de Trujillo. 2021 - Fernández Gutiérrez, Tania Solange (2022)
The present investigation entitled: Family climate and interpersonal relationships of students of the VI cycle of the Professional School of Social Work. National University of Trujillo. 2021, has as its main objective: Explain the influence of the family climate on the interpersonal relationships of the students, having as a hypothesis: The family climate significantly influences the interpersonal relationships of the students of the Professional School of Social Work of the VI cycle of the National University of Trujillo. The research was of a descriptive-correlational type, allowing the description of data and characteristics of the students and the measurement of variables. The sample was 50 students, applying the methods: inductive-deductive, analytical-synthetic, and statistical method. Using observation techniques, structured interview, and bibliographic compilation. The results show that the family climate of the students positively influences assertive interpersonal relationships; because in your home there are affective relationship and there is assertive communication, with their peers, active participation, optimal teamwork, assertive communication and the strengthening of student leadership are reflected. The family climate of the students negatively influences passive interpersonal relationships, reflected in the submission of the student, who does not give an opinion and accepts the orders of others, developing passive leadership, little participation and being highly influence. Finally, that the family climate of the students negatively influences aggressive interpersonal relationships, reflected in shouting, insults, conflicts, arguments, violence, and aggressive communication with family members, generating feelings of insecurity, resentment, impotence, hatred, not resolving conflicts, not respecting opinions and making fun of their peers.